أستخدام المصفوفة المميزة المعدلة وتوليفية عددية في تصميم أمثل لطالء مضاد لالنعكاس لركيزة سيلينيدات الخارصين - نزار, الاء; رشيد, هيفاء غازي; محسن, حركات (Al-Nahrain Journal of Science, 2018)
This work includes the design, performance, and applications of anti reflection coating (ARC) in the infrared spectral region.In this study the design ARC related to isotropic, homogenous and non-dispersive dielectric thin film material deposited on Zinc Selenide (ZnSe) as substrate for normal incident of light. For design this kind of coating with taking into account the above points we have been building theoretical model using software (Matlab). This modal based on Characteristic matrices and numerical synthesis optimal method.Results are very encouraging and indicate that this model is a robust and helpful model for antireflection coating design with ZnSe substrate. also in this paper we refer to the merit function that used.